Finite Element Analysis of a Deep Foundation Pit with Double-layer Internal Support Based on Midas - DONG Guihong; QIAN Xuexin (Renmin Zhujiang)
Taking a deep foundation pit with internal support in Kunming as the research object, and according to the environment, geological engineering conditions and hydrogeological conditions around the foundation pit, this paper establishes a three-dimensional numerical model for excavation of the foundation pit by the finite element software of Midas GTS NX to analyze the deformation and support force of the foundation pit during excavation, and compares the simulation results with the data monitored on site. The results show that the numerical simulation results of soil displacement and support pile displacement are consistent with the monitoring data. And the maximum monitoring data of support force does not exceed the simulation results. Therefore, with good reliability, the finite element simulation and analysis can provide reference for foundation pit monitoring.